Successful radiofrequency pulmonary vein isolation in a patient with pneumonectomy - Enes Elvin Gül; Cengiz Erol; Fethi Kılıçaslan (KARE Publishing, 2016)
Summary- Among electrophysiologic procedures, catheter ablation of atrial fibrillation (AF) is challenging, requiring the isolation of all pulmonary veins (PVs). AF is associated with serious complications including PV stenosis. Presently described was a technically challenging case of PV isolation in a patient with left-sided pneumonectomy due to lung cancer.